EFL Students’ Perception on the Use of “Rhetorical Précis” as a Summarizing Template - Wahyun Bardianing Panggalih; Bambang Yudi Cahyono (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2020)
For university students, a skill in writing a good summary of articles, books and other sources is very important. Rhetorical Précis, a summarizing template that consists of four dense and direct sentences, can be used to compose a precise summary. This research aims at exploring EFL students’ perceptions of the use of Rhetorical Précis. Using a survey study, a five-degree questionnaire was spread out to 47 students who had attended the Critical Reading course at a reputable university in Surabaya, Indonesia. The data from the questionnaire were analyzed quantitatively. In addition, a semi-structured interview was held with four of the students. The interview was recorded and transcribed to meet the need of this study. The findings of this study showed that most of the students had positive perceptions of each element of Rhetorical Précis. In short, the students perceived that the Rhetorical Précis summarizing template could be used  by the students to make a summary of the original texts precisely and accurately.